Method for preparing oil-soluble carbon dot-based afterglow luminescent material by one-step method

Through one-step high-temperature co-precipitation technology, nano-scale hydrophobic CDs@NaReF4 nanoparticles were prepared, which solved the problems of limited application of liquid carbon dot-based materials in the biological field and complicated preparation process in the prior art, and achieved stable dispersion and application expansion of materials.

CN119799330AActive Publication Date: 2025-04-11SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411703223.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-04-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing liquid phase carbon dot-based room temperature afterglow materials are limited in the biological field, and the preparation process is cumbersome, making it difficult to obtain stable and easy to surface modification nano-scale materials.

Method used

A one-step high-temperature co-precipitation strategy was adopted to react Re(CH3CO2)3 aqueous solution with oleic acid and 1-octene to generate NaReF4 matrix and carbon dots simultaneously embedded, and nanoscale hydrophobic CDs@NaReF4 nanoparticles were prepared.

Benefits of technology

The preparation of small-size, hydrophobic carbon dot-based afterglow luminescent materials is realized, and the materials are stablely dispersed in organic solvents, expanding the scope of application and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799330A_ABST
    Figure CN119799330A_ABST
Patent Text Reader

Abstract

The invention relates to the field of luminescent carbon nanomaterials, in particular to the technical field of preparation of fluorescent carbon dots (CDs), and particularly relates to a method for preparing an oil-soluble carbon dot-based afterglow luminescent material by a one-step method. According to the method, under the condition of high temperature, in-situ generated carbon dots are embedded into a rare earth fluoride NaReF4 matrix, and the prepared CDs and NaReF4 nano composite material can be uniformly and stably dispersed in an organic solvent and can emit green room-temperature afterglow with long service life under excitation of ultraviolet light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of luminescent carbon nanomaterials, in particular to the technical field of fluorescent carbon dots (CDs) preparation, and specifically to a one-step method for preparing oil-soluble carbon dot-based afterglow luminescent materials. Background Art

[0002] Carbon dots are a new type of zero-dimensional carbon nanomaterial that is approximately spherical and can emit multicolor fluorescence in the ultraviolet-visible light absorption region. They have attracted widespread attention due to their simple synthesis method, good photostability, good biocompatibility and low toxicity. In recent years, it has been found that embedding carbon dots into various matrices can effectively induce carbon dots to produce room temperature afterglow by inhibiting the non-radiative transition of molecules and protecting the triplet state of carbon dots. Carbon dot-based room temperature afterglow materials can eliminate the interference of background fluorescence and light scattering, and have the advantages of adjustable energy gap and simple structural design. They have broad application prospects in information encryption, sensing, fingerprint recognition and bioimaging.

[0003] So far, carbon dot-based room temperature afterglow has expanded from the main solid afterglow to water-soluble afterglow. After years of research, carbon dot-based room temperature afterglow materials with different lifetimes and emission wavelengths have been obtained. However, due to the inherent defects of composite materials, liquid phase CDs-based room temperature afterglow materials are still facing some challenges: for example, the composite materials obtained by the inorganic salt melting method and the rigid hydrogen bond network fixation method are often seriously hindered by their large particle size, which seriously hinders their further development in the biological field; the composite materials prepared by the SiO2 coating method have serious agglomeration due to the reaction between the large number of Si-OH hydrophilic groups on the SiO2 gel layer, resulting in slow development in the field of biomedical analysis and imaging. In addition, the controllable preparation of composite materials and the cumbersome surface modification process have also led to the research of liquid phase CDs-based room temperature afterglow materials being in the early stages. Therefore, it is of great significance to develop a new matrix that can stabilize the excited triplet state of CDs, has uniform size and morphology, and is easy to modify on the surface.

[0004] In response to this, existing technologies have gradually shifted their research focus from single materials to composite materials, and developed rare earth fluoride and CDs composite luminescent nanomaterials (CDs@rare earth fluorides). However, existing CDs@rare earth fluorides are mainly liquid carbon dot-based materials, which can only dissolve and react well in water-soluble solutions, but cannot fully dissolve and react in oil-soluble solutions, which limits the application of CDs@rare earth fluorides in oil-soluble reactions. In addition, the current size of CDs@rare earth fluorides can only reach the micron level, and the large micron-level CDs@rare earth fluorides are large in size and easily precipitate during the reaction, so that they cannot be stably dispersed on the corresponding materials, affecting the afterglow emission effect of the material. In addition, the existing preparation methods of CDs@rare earth fluorides usually adopt a multi-step synthesis method of in-situ growth, self-assembly and intermediate medium bridging to obtain multifunctional nanocomposites, and the preparation process is complicated. It can be seen that obtaining hydrophobic afterglow with excellent stability in carbon dot-based materials is still a huge challenge. Summary of the invention

[0005] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material. The method can produce a small-sized hydrophobic carbon dot-based afterglow luminescent material. The hydrophobic carbon dot-based afterglow luminescent material has the advantage of stable afterglow luminescence, and the method has the advantage of easy operation.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material is provided, comprising the following steps:

[0008] S1, adding Re(CH3CO2)3 aqueous solution, oleic acid and 1-octadecene into a container, mixing them evenly to obtain a first mixed solution;

[0009] S2, heating the first mixed solution to 120°C to 180°C, adding citrate after reacting for 0.3h to 1h, and stopping heating;

[0010] S3, after cooling the first mixed solution to room temperature, adding NaOH methanol solution and NH4F methanol solution, mixing evenly, to obtain a second mixed solution;

[0011] S4, adding the second mixed solution to 40°C-60°C and keeping the temperature for 0.4h-0.6h, then continuing to raise the temperature to 100°C-110°C and performing vacuum treatment;

[0012] S5, raising the temperature of the second mixed solution to 280° C. to 320° C., and then introducing a nitrogen atmosphere to continue the reaction for 1 h to 3 h;

[0013] S6. Stop heating, allow the second mixed solution to cool naturally to room temperature, add ethanol solution and cyclohexane solution and mix evenly, then let it stand to obtain precipitated NH4F methanol solution CDs@NaReF4 nanoparticles, collect the CDs@NaReF4 nanoparticles and wash them to obtain hydrophobic carbon dot-based afterglow luminescent material.

[0014] In some embodiments, in S1, 7 ml to 12 ml of oleic acid and 10 ml to 18 ml of 1-octadecene are added per mole of Re(CH3CO2)3 aqueous solution.

[0015] In some embodiments, in S2, 2-5 mg of citrate is added per ml of the first mixed solution.

[0016] In some embodiments, in S3, 0.1 mmol to 0.3 mmol of NaOH methanol solution and 0.12 mmol to 0.18 mmol of NH 4 F methanol solution are added per milliliter of the first mixed solution.

[0017] In some embodiments, in S4, the vacuum treatment step includes connecting a vacuum pump to a double-row tube, and the double-row tube degassing the second mixed solution for 15 to 20 minutes.

[0018] In some embodiments, in S6, the static treatment method includes: centrifuging the second mixed solution in a centrifuge at a centrifuge speed of 8000 rpm to 12000 rpm; and the centrifugation time is 3 min to 10 min.

[0019] In some embodiments, in S6, the washing step includes: washing the CDs@NaReF4 nanoparticles with an ethanol solution and a cyclohexane solution in sequence, repeating the process three times, and dispersing the obtained hydrophobic carbon dot-based afterglow luminescent material in a cyclohexane solution for storage.

[0020] The beneficial effects of the one-step method for preparing oil-soluble carbon dot-based afterglow luminescent materials of the present invention are as follows:

[0021] (1) The present invention provides a one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material. The method can react with carbon dots in a Re(CH3CO2)3 aqueous solution, so that a NaReF4 matrix and carbon dots are generated simultaneously and the carbon dots are embedded in the NaReF4 matrix at the same time, thereby obtaining a new material CDs@NaReF4 nanoparticles of small nanometer size. The method is easy to operate, has the advantages of low cost, and is suitable for large-scale production and application.

[0022] (2) The present invention provides a one-step method for preparing oil-soluble carbon dot-based afterglow luminescent materials. Since the obtained CDs@NaReF4 particles are of nanometer size, it overcomes the problem that traditional micrometer-sized CDs@rare earth fluorides are large in size and cannot be stably dispersed in the material, resulting in unstable afterglow emission.

[0023] (3) The present invention provides a one-step method for preparing oil-soluble carbon dot-based afterglow luminescent materials. The surface of the obtained CDs@NaReF4 particles contains a large amount of oleic acid ligands, which are hydrophobic. This makes the CDs@NaReF4 particles hydrophobic and can be stably dispersed in organic solutions, expanding the application range of the CDs@NaReF4 particles, so that the CDs@NaReF4 particles are no longer limited to aqueous solution materials.

[0024] Also provided is an oil-soluble carbon dot-based afterglow luminescent material, which is prepared by the one-step method for preparing the oil-soluble carbon dot-based afterglow luminescent material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following is a brief introduction to the drawings required for describing the embodiment:

[0026] Figure 1 This is a scanning electron microscope image of the CDs@NaYF4 composite material synthesized in Experimental Example 1.

[0027] Figure 2 This is a transmission electron microscope image of the CDs@NaYF4 composite material synthesized in Experimental Example 1.

[0028] Figure 3 The fluorescence emission spectrum, afterglow excitation / emission spectrum and afterglow lifetime decay curve of the CDs@NaYF4 composite material synthesized in Experimental Example 1 were measured after being dispersed in a cyclohexane solution.

[0029] Figure 4 These are sample photos of the CDs@NaYF4 composite material synthesized in Experimental Example 1, dispersed in organic solvents of cyclohexane, dichloromethane and acetic acid, and ultrasonically treated for 30 minutes, with the fluorescent lamp and 365nm ultraviolet lamp turned on and off. DETAILED DESCRIPTION

[0030] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0031] The terminology used in the present invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the present invention.

[0032] Example 1

[0033] The present invention discloses a one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material, comprising the following steps:

[0034] S1, adding Re(CH3CO2)3 aqueous solution, oleic acid and 1-octadecene into a container, mixing them evenly to obtain a first mixed solution,

[0035] In the above steps, Re(CH3CO2)3 has good size, morphology and monodispersity. At present, NaReF4 crystals with a size of less than 50nm can be obtained by a simple coprecipitation method, and Re(CH3CO2)3 has a wide source. 3+ Oleic acid and 1-octadecene are a solution, which is used as a reaction solvent and also a surfactant. They play a certain role in the crystal growth size of the NaReF4 matrix during the reaction and provide hydrophobic groups.

[0036] S2. Heat the first mixed solution to 120-180° C., preferably 160° C., react for 0.3-1 h, preferably 0.5 h, add citrate, and stop heating, wherein 2-5 mg of citrate, preferably 4 mg, is added per ml of the first mixed solution.

[0037] In the above steps, citrate is mainly used as a precursor of carbon dots (CDs).

[0038] S3, after the first mixed solution is cooled to room temperature, NaOH methanol solution and NH4F methanol solution are added, and mixed evenly to obtain a second mixed solution, wherein 0.1-0.3 mmol of NaOH methanol solution, preferably 0.2 mmol, and 0.12-0.18 mmol of NH4F methanol solution, preferably 0.15 mmol, are added per milliliter of the first mixed solution;

[0039] In the above steps, the addition of NaOH methanol solution is mainly for the introduction of Na ions, while the addition of NH4F methanol solution is for the addition of F ions.

[0040] S4, adding the second mixed solution to 40-60° C., preferably 50° C., and keeping the temperature for 0.4-0.6 h, preferably 0.5 h, and then continuing to raise the temperature to 100-110° C., preferably 105° C., and performing vacuum treatment;

[0041] In the above steps, each substance is allowed to react sufficiently.

[0042] S5, raising the temperature of the second mixed solution to 280-320° C., preferably 300° C., and then introducing a nitrogen atmosphere to continue the reaction for 1-3 hours, preferably 2 hours;

[0043] S6. Stop heating, allow the second mixed solution to cool naturally to room temperature, add ethanol solution and cyclohexane solution for washing, let it stand after mixing to obtain precipitated NH4F methanol solution CDs@NaReF4 nanoparticles, collect the CDs@NaReF4 nanoparticles for washing, and obtain oil-soluble carbon dot-based afterglow luminescent material.

[0044] In the above steps, after the reaction is completed, the ethanol solution is added mainly to precipitate the CDs@NaReF4 nanoparticles so that the nanoparticles can be separated from the solvent by centrifugation later; the cyclohexane solution is added mainly to remove oleic acid and 1-octadecene that do not participate in the reaction.

[0045] In this embodiment, in S4, the vacuum treatment step includes connecting a vacuum pump to a double-row tube, and the double-row tube degasses the second mixed solution for 15 to 20 minutes, preferably 16 minutes.

[0046] In this embodiment, in S6, the method of static treatment after mixing includes: centrifuging the second mixed solution in a centrifuge, the centrifugal speed is 8000-12000 rpm, preferably 10000 rpm; the centrifugal time is 3-10 minutes, preferably 5 minutes.

[0047] In this embodiment, in S6, the washing step includes: washing with an ethanol solution and a cyclohexane solution in sequence, and repeating the process three times, and dispersing the obtained oil-soluble carbon dot-based afterglow luminescent material in a cyclohexane solution for storage.

[0048] The above method is a method for preparing hydrophobic carbon dot-based afterglow luminescent materials through a one-step high-temperature co-precipitation strategy. Under high temperature conditions, the in-situ generated carbon dots are embedded in the rare earth fluoride (NaReF4) matrix, and the prepared CDs@NaReF4 nanocomposite material can be uniformly and stably dispersed in some organic solvents, and can emit a long-life green room temperature afterglow under the excitation of ultraviolet light.

[0049] The above-mentioned one-step method for preparing oil-soluble carbon dot-based afterglow luminescent material CDs@NaReF4 nanocomposite material can be uniformly and stably dispersed in some organic solvents, and can emit long-life green room-temperature afterglow under the excitation of ultraviolet light. Through the spatial confinement effect of NaReF4 matrix on carbon dots, the afterglow emission of carbon dot-based room-temperature afterglow material under ultraviolet light excitation is realized.

[0050] Test Example 1

[0051] To further illustrate the performance of the material obtained by the method of the present invention, the following test example 1 is carried out: specifically comprising the following steps:

[0052] (1) First, prepare a 50 mL two-necked round-bottom flask, then add 0.4 mmol of Y(CH3CO2)3 solution, 4 mL of oleic acid and 7 mL of 1-octadecene.

[0053] (2) The flask was placed in a heating device, and the mixed solution was heated to 150° C. under stirring. After reacting at 150° C. for 0.5 h, 30 mg of magnesium citrate was added and the heating was stopped.

[0054] (3) After the mixed solution was cooled to room temperature, 1 mmol of NaOH methanol solution and 1.32 mmol of NH4F methanol solution were added.

[0055] (4) The temperature of the mixed solution was raised to 50°C and maintained at this temperature for 0.5 h.

[0056] (5) Continue to raise the temperature to 110°C and degas for 20 minutes under vacuum conditions using a vacuum pump and a double-row tube.

[0057] (6) Finally, the mixed solution was heated to 310 °C and reacted for 1.5 h under a nitrogen atmosphere.

[0058] (7) Stop heating, cool the mixed solution to room temperature, add ethanol solution and cyclohexane solution, and centrifuge (10000 rpm, 5 min) to obtain precipitated CDs@NaYF4 nanoparticles.

[0059] (8) Washing was continued three times with ethanol solution and cyclohexane solution, and the hydrophobic CDs@NaYF4 composite material obtained by the reaction was redispersed in the cyclohexane solution.

[0060] Performance Test:

[0061] The CDs@NaYF4 composite material obtained in Experimental Example 1 was tested for performance, and the following results were obtained:

[0062] Figure 1 This is a scanning electron microscope image of the CDs@NaYF4 composite material synthesized in Experimental Example 1. From the image, we can see the morphology and size of the material, which is a spherical shape with raised surface, uniform particle size distribution, and an average particle size of about 200nm. It can be seen that the size of the CDs@NaYF4 composite material prepared by the present invention can reach the nanometer level, can be more stably dispersed in the medium, and improves the dispersion stability of the CDs@NaYF4 composite material in the application material.

[0063] Figure 2This is a transmission electron microscope image of the CDs@NaYF4 composite material synthesized in Experimental Example 1, which corresponds to the sample morphology and size in the scanning electron microscope image, further illustrating that the size of the CDs@NaYF4 composite material prepared in the present invention can reach the nanometer level.

[0064] Figure 3 The fluorescence spectrum and afterglow excitation / emission spectrum of the CDs@NaYF4 composite material synthesized in Experimental Example 1 were measured under different excitation wavelengths after being dispersed in a cyclohexane solution, as well as the afterglow lifetime decay curve measured at 365nm excitation and 520nm emission. From the fluorescence emission spectrum, it can be seen that the maximum fluorescence emission peak of CDs@NaYF4 is located at about 470nm; the afterglow emission spectrum under different excitation wavelengths shows that the composite material has a double peak emission, which is approximately located near 470nm and 520nm; by performing a three-exponential fitting on the afterglow lifetime decay curve excited at 360nm, it can be obtained that the afterglow lifetime of the composite material is 530ms. It can be seen that the CDs@NaYF4 composite material prepared by the present invention can stably emit afterglow.

[0065] Figure 4 The CDs@NaYF4 composite material synthesized in Experimental Example 1 is dispersed in organic solvents of cyclohexane, dichloromethane and acetic acid and subjected to ultrasonic treatment for 30 minutes, and then the fluorescent lamp and 365nm ultraviolet lamp are turned on and off. After the ultraviolet lamp is turned off, an obvious afterglow phenomenon can be observed, indicating that the composite material has good stability in organic solvents and can be applied in some special environments. It can be seen that the CDs@NaYF4 composite material prepared by the present invention is hydrophobic.

[0066] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the equivalent replacement of each raw material in the method of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention without departing from the principle of the present invention.

Claims

1. A one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material, characterized in that: The following steps are included: S1, adding Re(CH3CO2)3 aqueous solution, oleic acid and 1-octadecene into a container, mixing them evenly to obtain a first mixed solution; S2, heating the first mixed solution to 120°C to 180°C, adding citrate after reacting for 0.3h to 1h, and stopping heating; S3, after cooling the first mixed solution to room temperature, adding NaOH methanol solution and NH4F methanol solution, mixing evenly, to obtain a second mixed solution; S4, adding the second mixed solution to 40°C-60°C and keeping the temperature for 0.4h-0.6h, then continuing to raise the temperature to 100°C-110°C and performing vacuum treatment; S5, raising the temperature of the second mixed solution to 280° C. to 320° C., and then introducing a nitrogen atmosphere to continue the reaction for 1 h to 3 h; S6. Stop heating, allow the second mixed solution to cool naturally to room temperature, add ethanol solution and cyclohexane solution and mix evenly, then let it stand to obtain precipitated NH4F methanol solution CDs@NaReF4 nanoparticles, collect the CDs@NaReF4 nanoparticles and wash them to obtain hydrophobic carbon dot-based afterglow luminescent material.

2. The method for preparing an oil-soluble carbon dot-based afterglow luminescent material in one step according to claim 1, characterized in that: In S1, 7 ml to 12 ml of oleic acid and 10 ml to 18 ml of 1-octadecene are added per mole of Re(CH3CO2)3 aqueous solution.

3. The method for preparing an oil-soluble carbon dot-based afterglow luminescent material in one step according to claim 1, characterized in that: In S2, 2 to 5 mg of citrate is added to each milliliter of the first mixed solution.

4. The method for preparing an oil-soluble carbon dot-based afterglow luminescent material in one step according to claim 1, characterized in that: In S3, 0.1 mmol to 0.3 mmol of NaOH methanol solution and 0.12 mmol to 0.18 mmol of NH4F methanol solution are added to each milliliter of the first mixed solution.

5. The method for preparing an oil-soluble carbon dot-based afterglow luminescent material in one step according to claim 1, characterized in that: In S4, the vacuum treatment step includes connecting a vacuum pump to a double-row tube, and the double-row tube degasses the second mixed solution for 15 to 20 minutes.

6. The one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S6, the static treatment method includes: centrifuging the second mixed solution in a centrifuge, the centrifugal speed is 8000 rpm to 12000 rpm, and the centrifugal time is 3 min to 10 min.

7. The one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material according to claim 1, characterized in that: In S6, the washing step includes: washing the CDs@NaReF4 nanoparticles with an ethanol solution and a cyclohexane solution in sequence, repeating the process three times, and dispersing the obtained hydrophobic carbon dot-based afterglow luminescent material in a cyclohexane solution for storage.

8. An oil-soluble carbon dot-based afterglow luminescent material, characterized in that: The material is prepared by the one-step method for preparing an oil-soluble carbon dot-based afterglow luminescent material as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • NaYF4 and carbon dot nano composite material and preparation method and applications thereof

    CN108893102A

  • NaYF4:Eu@CDs composite material, and preparation method and application thereof

    CN109294577A

  • Preparation method and application of graphene quantum dot-rare earth up-conversion compound

    CN111607388A

  • Carbon dot-based room-temperature phosphorescent composite material suitable for near-infrared excitation as well as preparation method, application and using method of carbon dot-based room-temperature phosphorescent composite material

    CN113583666A

  • Optical anti-counterfeiting method

    CN113698934A